Sea glass summer - Cannell, Dorothy (Severn House, 2012)
Recovering from a painful divorce, Sarah Draycott has moved to picturesque village of Sea Glass on the Maine coast to make a fresh start. As she finds herself increasingly caught up in the lives of the Sea Glass residents, Sarah finds her broken heart beginning to heal.